Silicon-carbon composite material as well as preparation method and application thereof
By adopting a three-layer composite structure of silicon carbon composite material, the silicon particles are covered with elastic carbon and porous carbon frames, the particle crushing problem caused by volume expansion of the silicon material is solved, and better electrochemical performance and cyclic performance are achieved.
Patent Information
- Application Number
- CN202411762287.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The volume expansion of silicon material during lithium embedding process leads to particle breakage, affecting the reversible capacity and service life of the battery. It is difficult for the existing technology to effectively solve this problem.
A silicon-carbon composite material with a three-layer composite structure is used. The first cladding layer is composed of elastic carbon and the second cladding layer is a porous carbon frame. This structural design effectively prevents the breakage of silicon particles during the process and work process.
It improves the electrochemical and cyclic properties of silicon materials, ensures the integrity of silicon particles, and extends the service life of the battery.
Smart Images

Figure BDA0005168012140000091 
Figure BDA0005168012140000101 
Figure FDA0005168012110000011
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery negative electrode materials, and in particular to silicon-carbon composite materials and preparation methods and applications thereof. Background Art
[0002] As awareness of low-carbon and environmental protection gradually increases, the new energy industry has become an important development direction in the energy field, new energy technology continues to advance, and the scale of the industry has further expanded. At present, whether it is conventional consumer batteries or power batteries with increasing demand, the entire industry has put forward higher requirements for battery energy density. The negative electrode material is directly related to the energy density of the battery, and the actual capacity of conventional graphite negative electrodes is close to its theoretical limit and cannot meet people's needs. Compared with graphite, the theoretical gram capacity of silicon can reach 3579mAh / g, which is more than ten times that of graphite, so it has become the most promising negative electrode material at present.
[0003] Due to factors such as lithium embedding capacity and phase transition, the volume expansion of silicon materials has become an important problem that plagues R&D personnel. This huge volume change can cause the silicon particles to break, resulting in a rapid decrease in the reversible capacity of the battery and affecting the service life. Nano-sizing is a major way to solve the volume expansion of silicon materials, but nanomaterials with large specific surface areas are prone to agglomeration, affecting performance. In addition, there are attempts to compound silicon with graphite or other carbon materials to improve the performance of silicon materials, but it is often difficult to support the long-term expansion and contraction of silicon materials, and the improvement in cycle performance is not obvious. Moreover, these methods often focus on the selection of raw materials, and how to design the structure of the material to prevent the breakage of silicon particles has not been perfected. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a silicon-carbon composite material and a preparation method and application thereof, wherein the silicon-carbon composite material adopts a novel structural design and can effectively solve the problem of silicon particle breakage.
[0005] In a first aspect of the present application, a silicon-carbon composite material is provided, the silicon-carbon composite material comprising:
[0006] Carbon-silicon composite particles, the carbon-silicon composite particles comprising silicon particles and a first coating layer coating the silicon particles, the first coating layer comprising elastic carbon, and the carbon-silicon composite particles recovering a deformation S of ≥80% after the load is removed;
[0007] A second coating layer, wherein the second coating layer coats the carbon-silicon composite particles, and the second coating layer comprises a porous carbon framework.
[0008] The deformation recovery of the carbon-silicon composite particles is detected by nanoindentation, and any nanoindenter can be selected for detection.
[0009] In some embodiments of the present application, the silicon particles are at least one of nano-silicon particles and micro-silicon particles.
[0010] In some embodiments of the present application, the particle size of the silicon particles is 0.1 nm to 500 μm, for example, 0.1 nm, 0.2 nm, 0.5 nm, 1 nm, 2 nm, 5 nm, 10 nm, 20 nm, 50 nm, 100 nm, 200 nm, 500 nm, 1 μm, 2 μm, 5 μm, 10 μm, 20 μm, 50 μm, 100 μm, 200 μm, 500 μm. In some embodiments, the particle size of the silicon particles is 1 nm to 100 μm, 2 nm to 10 μm, 5 nm to 500 nm, 5 nm to 300 nm, 10 nm to 200 nm, 100 nm to 10 μm.
[0011] In some embodiments of the present application, the thickness H1 of the first coating layer is 20 to 40 nm, for example, it can be 20 nm, 25 nm, 30 nm, 35 nm, 40 nm.
[0012] In some embodiments of the present application, the thickness H2 of the second coating layer is 100 to 200 nm, for example, it can be 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm.
[0013] In some embodiments of the present application, the silicon particles are doped SiC x (0 < x ≤ 1) Si particles.
[0014] In some embodiments of the present application, the elastic modulus of the first coating layer is T1, the elastic modulus of the second coating layer is T2, the self-expansion rate Z of the silicon particles ≥ 300%, and the silicon-carbon composite material satisfies the following relationship: In the relationship, H1 and H2 are numerical values omitting the unit of measurement in nm, T1 and T2 are numerical values omitting the unit of measurement in GPa, and Z is the actual value in percentage.
[0015] Among them, the measurement methods of the elastic modulus T1 and the elastic modulus T2 of the first coating layer and the second coating layer are to measure the surface elastic modulus of the silicon-carbon composite particles and the silicon-carbon composite material respectively by nanoindentation method, which are the elastic moduli of the first coating layer and the second coating layer.
[0016] By observing the formed silicon-carbon composite material with a high-magnification transmission electron microscope, it can be seen that there is an obvious boundary between the silicon particles, the first coating layer and the second coating layer. Therefore, the thickness H1 of the first coating layer and the thickness H2 of the second coating layer can be directly measured by a high-magnification transmission electron microscope.
[0017] The self-expansion rate Z of silicon particles is measured as follows:
[0018] Referring to the preparation and testing of the soft-pack battery in the example, pure silicon was used instead of the silicon-carbon composite material to prepare the battery of the same specification, and the battery after 300 cycles at 25°C was disassembled in the glove box, and the negative electrode was cleaned with diethyl carbonate (DEC) and the thickness of the electrode was measured. Self-expansion rate = (thickness of the electrode after the cycle - thickness of the electrode before the cycle) / thickness of the electrode before the cycle × 100%.
[0019] In some embodiments of the present application, Z is 300%. As stated in Li Chunxiao's "Progress in Research on Lithium-ion Battery Materials", silicon materials expand severely during charge / discharge, with a volume change of up to 300%.
[0020] In some embodiments of the present application, the elastic modulus T1 of the first coating layer is 40 to 80 GPa, for example, 40 GPa, 50 GPa, 60 GPa, 70 GPa, or 80 GPa.
[0021] In some embodiments of the present application, the elastic modulus T2 of the second coating layer is 8 to 15 GPa, for example, it may be 8 GPa, 9 GPa, 10 GPa, 11 GPa, 12 GPa, 13 GPa, 14 GPa, or 15 GPa.
[0022] The silicon-carbon composite material according to the embodiment of the present application has at least the following beneficial effects:
[0023] The silicon-carbon composite material in the embodiment of the present application adopts a three-layer composite structure, wherein the first coating layer is used as a buffer layer, which has both high elasticity and high conductivity, and the second coating layer is used as a protective layer, which has high hardness, high conductivity and high specific surface area. This not only improves the material properties of silicon, but also ensures the integrity of silicon particles during the process and working process, effectively preventing them from breaking.
[0024] Specifically, the elastic carbon of the first coating layer has high elasticity and high Li +Diffusion coefficient, high elasticity provides a certain buffering effect, which can protect silicon particles, while providing stable contact between silicon and carbon layers, and maintaining a stable electrode / electrolyte interface during long-term cycles to avoid excessive SEI growth; in the second coating layer, the carbon framework has high hardness and high stability, which can provide certain structural support for the material to prevent the material from breaking during the process; and the porous structure increases the specific surface area of the material and can also improve the ionic conductivity of the material. During rolling, the outermost porous carbon framework is stressed first. If it is broken by excessive force, the highly elastic carbon layer will provide a certain buffering capacity as a protective layer to prevent the silicon core from breaking, and at the same time it can also restrain the expansion of silicon during the reaction. In this way, two protective layers are constructed outside the core of the silicon particles to prevent the silicon particles from breaking during the process. The silicon-carbon composite material obtained in this way not only has excellent electrochemical performance advantages, but also the integrity of the particles enables it to provide better cycle performance.
[0025] In a second aspect of the present application, a method for preparing a silicon-carbon composite material is provided, comprising the following steps:
[0026] coating the surface of silicon particles with a first carbon source and carbonizing the particles to obtain carbon-silicon composite particles;
[0027] The carbon-silicon composite particles are mixed with a second carbon source and a pore-forming agent, freeze-dried, and calcined to form a second coating layer to obtain the silicon-carbon composite material.
[0028] In some embodiments of the present application, coating the first carbon source on the surface of the silicon particles comprises:
[0029] mixing a first carbon source with a first solvent to obtain a coating solution;
[0030] The silicon particles are mixed with the coating solution and stirred, and the first solvent is evaporated to allow the first carbon source to coat the surface of the silicon particles.
[0031] In some embodiments of the present application, the mass volume ratio of the first carbon source to the first solvent is (0.1-0.5) g:15 mL, for example, 0.1 g, 0.15 g, 0.2 g, 0.25 g, 0.3 g, 0.35 g, 0.4 g, 0.45 g, 0.5 g of the first carbon source can be mixed with 15 mL of the first solvent. When the proportion of the first carbon source decreases, the carbon material proportion decreases, which will attenuate the performance; when the proportion of the first carbon source increases, the increase in carbon material will cause elastic failure, form a hardened carbon framework, and hinder the performance of the silicon particles.
[0032] In some embodiments of the present application, the silicon particles and the coating solution are mixed and stirred for 8 to 16 hours.
[0033] In some embodiments of the present application, the mass volume ratio of the first carbon source to the first solvent is about 0.2 g:15 mL.
[0034] In some embodiments of the present application, the first solvent includes toluene.
[0035] In some embodiments of the present application, the first carbon source is asphalt.
[0036] In some embodiments of the present application, the asphalt is selected from at least one of petroleum asphalt, coal asphalt, and natural asphalt.
[0037] In some embodiments of the present application, the mass ratio of the first carbon source to the silicon particles is (1-9):3, for example, 1:3, 2:3, 1:1, 4:3, 5:3, 2:1, 7:3, 8:3, or 3:1.
[0038] In some embodiments of the present application, the carbonization temperature is 500-1000°C, for example, 500°C, 600°C, 700°C, 800°C, 900°C, or 1000°C.
[0039] In some embodiments of the present application, the carbonization time is 15 min to 4 h, for example, it can be 15 min, 30 min, 45 min, 1 h, 2 h, 3 h, or 4 h.
[0040] In some embodiments of the present application, the mass ratio of the second carbon source to the pore-forming agent is 1:(0.1-0.5), for example, it can be 1:0.1, 1:0.2, 1:0.3, 1:0.4, or 1:0.5.
[0041] In some embodiments of the present application, the second carbon source includes at least one of polyvinyl pyrrolidone, polyvinyl alcohol, sucrose, glucose, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyethylene glycol.
[0042] In some embodiments of the present application, the pore-forming agent includes at least one of NaCl, KCl, urea, and ammonium bicarbonate.
[0043] In some embodiments of the present application, the pore former includes NaCl and urea.
[0044] In some embodiments of the present application, the freeze-drying temperature is -90 to -20°C, for example, it can be -90°C, -80°C, -70°C, -60°C, -50°C, -40°C, -30°C, or -20°C.
[0045] In some embodiments of the present application, freeze drying comprises freezing at the aforementioned temperature for 8 to 24 hours and then vacuum drying.
[0046] In some embodiments of the present application, the vacuum drying time is 24 to 72 hours.
[0047] In some embodiments of the present application, the calcination temperature is 500 - 800 °C, for example, it can be 500 °C, 600 °C, 700 °C, 800 °C.
[0048] In some embodiments of the present application, the calcination time is 3 - 12 h.
[0049] In some embodiments of the present application, the silicon-carbon composite material prepared by the above preparation method includes a multi-layer structure. The multi-layer structure includes, from the inside out, silicon particles, a first coating layer, and a second coating layer. The first coating layer includes elastic carbon, and the second coating layer includes a porous carbon framework.
[0050] In some embodiments of the present application, the silicon particles are at least one of nano-silicon particles and micro-silicon particles.
[0051] In some embodiments of the present application, the particle size of the silicon particles is 0.1 nm - 500 μm, for example, it is 0.1 nm, 0.2 nm, 0.5 nm, 1 nm, 2 nm, 5 nm, 10 nm, 20 nm, 50 nm, 100 nm, 200 nm, 500 nm, 1 μm, 2 μm, 5 μm, 10 μm, 20 μm, 50 μm, 100 μm, 200 μm, 500 μm. In some embodiments, the particle size of the silicon particles is 1 nm - 100 μm, 2 nm - 10 μm, 5 nm - 500 nm, 5 nm - 300 nm, 10 nm - 200 nm, 100 nm - 10 μm.
[0052] In some embodiments of the present application, the thickness H1 of the first coating layer is 20 - 40 nm, for example, it can be 20 nm, 25 nm, 30 nm, 35 nm, 40 nm.
[0053] In some embodiments of the present application, the thickness H2 of the second coating layer is 100 - 200 nm, for example, it can be 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm.
[0054] In some embodiments of the present application, the silicon particles are doped SiC x (0 < x ≤ 1) Si particles.
[0055] In some embodiments of the present application, the elastic modulus of the first coating layer is T1, the elastic modulus of the second coating layer is T2, the self-expansion rate Z of the silicon particles ≥ 300%, and the silicon-carbon composite material satisfies the following relationship: In the relationship, H1 and H2 are numerical values omitting the unit of measurement in nm, T1 and T2 are numerical values omitting the unit of measurement in GPa, and Z is the actual value in percentage.
[0056] In some embodiments of the present application, the elastic modulus T1 of the first coating layer is 40 to 80 GPa, and for example, it can be 40 GPa, 50 GPa, 60 GPa, 70 GPa, 80 GPa.
[0057] In some embodiments of the present application, the elastic modulus T2 of the second coating layer is 8 to 15 GPa, and for example, it can be 8 GPa, 9 GPa, 10 GPa, 11 GPa, 12 GPa, 13 GPa, 14 GPa, 15 GPa.
[0058] It can be understood that during the carbonization process of forming the first coating layer, some of the elastic carbon will further react with the silicon particles to generate SiC x (0 < x ≤ 1). Therefore, the internal silicon particles are actually Si particles doped with SiC x particles.
[0059] The preparation method of the silicon-carbon composite material according to the embodiments of the present application has at least the following beneficial effects:
[0060] The freeze-drying method is used to prepare the carbon framework precursor. Compared with evaporation, this method is carried out in a low-temperature environment, avoiding over-baking from affecting the quality of substances, so that the humidity of the material can be better controlled, and the occurrence of side reactions is prevented, reducing impurities in the precursor. In this way, many properties including cycle performance can be effectively improved, especially the cycle performance in the long term.
[0061] The finally prepared silicon-carbon composite material has a three-layer composite structure. The first coating layer serves as a buffer layer, having both high elasticity and high conductivity. The second coating layer serves as a protective layer and simultaneously has high hardness, high conductivity, and high specific surface area. This can not only improve the material properties of the silicon particles as the innermost core, but also ensure the integrity of the silicon particles during the process and operation, effectively preventing breakage. During rolling, the outermost porous carbon framework is stressed first. If it breaks due to excessive stress, the high-elasticity carbon layer as a protective layer will provide a certain buffering ability to prevent the Si core from breaking, and it can also restrain the expansion of Si during the reaction.
[0062] In the third aspect of the present application, a secondary battery is provided, and the secondary battery includes the aforementioned silicon-carbon composite material, or the silicon-carbon composite material prepared by the aforementioned preparation method.
[0063] In some embodiments of the present application, the secondary battery includes a positive electrode, a negative electrode, and a separator located between the positive electrode and the negative electrode.
[0064] The negative electrode includes a negative electrode current collector and a negative electrode active layer located on the negative electrode current collector, the negative electrode active layer includes a positive electrode active material, and the positive electrode active material includes any of the aforementioned silicon-carbon composite materials. The positive electrode includes a positive electrode current collector and a positive electrode active layer located on the positive electrode current collector, the positive electrode active layer includes a positive electrode active material, such as at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, nickel cobalt manganese oxide, nickel cobalt aluminum oxide, and nickel manganese aluminum oxide.
[0065] In some embodiments of the present application, a secondary battery includes a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and an electrolyte.
[0066] In some embodiments of the present application, the electrolyte is a solid electrolyte or an electrolyte.
[0067] In some embodiments of the present application, the positive electrode active layer / negative electrode active layer further includes at least one of a conductive agent and a binder. The conductive agent includes but is not limited to at least one of graphite, acetylene black, carbon black, carbon nanotubes, carbon fibers, etc. The binder includes but is not limited to at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyurethane (PU), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), etc.
[0068] In some embodiments of the present application, the positive electrode active layer / negative electrode active layer includes 70-99wt% of positive electrode active material / negative electrode active material, 0.5-6wt% of conductive agent and 0.5-20wt% of binder. In some embodiments, the mass fraction of the positive electrode active material in the positive electrode active layer / negative electrode active layer is 80-99wt%, 90-99wt%, 95-99wt%; the mass fraction of the conductive agent in the positive electrode active layer / negative electrode active layer is 1-6wt%, 2-5wt%; the mass fraction of the binder in the positive electrode active layer / negative electrode active layer is 1-10wt%, 1-5wt%.
[0069] In some embodiments of the present application, when the positive electrode active material / negative electrode active material, the conductive agent and the binder are made into the positive electrode active layer / negative electrode active layer, the positive electrode active layer / negative electrode active layer is prepared by dispersing the positive electrode active material / negative electrode active material, the conductive agent and the binder in a solvent and then coating the positive electrode active layer / negative electrode active layer on the positive electrode current collector / negative electrode current collector and drying the same. In some of these embodiments, the solvent may be N-methylpyrrolidone (NMP) or other optional solvents.
[0070] In some embodiments of the present application, the positive electrode collector / negative electrode collector includes at least one of a metal foil (such as aluminum foil, silver foil, tin foil, iron foil, titanium foil, nickel foil, copper foil or alloy foil of the above metals), a metal mesh (such as aluminum mesh, silver mesh, tin mesh, iron mesh, titanium mesh, nickel mesh, copper mesh or alloy mesh of the above metals).
[0071] In some embodiments of the present application, the separator includes, but is not limited to, a single-layer or multi-layer film of one or more materials selected from the group consisting of polyethylene (PE), polypropylene (PP), and polyvinylidene fluoride (PVDF).
[0072] In some embodiments of the present application, the secondary battery includes a bare cell, and the bare cell is formed by a positive electrode, a negative electrode, and a separator through at least one of winding, lamination, etc.
[0073] In some embodiments of the present application, a secondary battery includes a bare cell and a shell encapsulating the bare cell.
[0074] In some embodiments of the present application, the outer shell is a soft shell or a hard shell.
[0075] In some embodiments of the present application, a secondary battery is obtained by injecting an electrolyte into a shell that wraps a bare battery core and then sealing it.
[0076] In a fourth aspect of the present application, an electrical device is provided, the electrical device comprising the aforementioned secondary battery.
[0077] Among them, electrical equipment refers to any equipment that can use electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Among them, it includes but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles can be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0078] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 is a cross-sectional view of a silicon-carbon composite material in an embodiment of the present application.
[0080] Reference numerals: silicon particles 100 , first coating layer 200 , second coating layer 300 . DETAILED DESCRIPTION
[0081] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.
[0082] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.
[0083] In the description of this application, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, "above", "below", "within", etc. are understood to include the number itself, and "about" means within the range of ±20%, 10%, 8%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.2%, 0.1%, etc. of the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0084] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0085] The present application is further described below with reference to specific examples.
[0086] Example 1
[0087] This embodiment provides a silicon-carbon composite material, referring to Figure 1 , shows the multilayer structure of the silicon-carbon composite material in the embodiment of the present application, which includes, from the inside to the outside, the innermost silicon particle 100, a first coating layer 200 formed by elastic carbon on the surface of the silicon particle 100, the two together constitute a silicon-carbon composite particle, and a second coating layer 300 formed by a porous carbon framework on the surface of the first coating layer 200 of the silicon-carbon composite particle.
[0088] The preparation method of the silicon-carbon composite material of this embodiment is as follows:
[0089] (1) Dissolve 0.2 g of asphalt in 15 mL of toluene to form an asphalt coating solution.
[0090] (2) Disperse 0.6 g of nano-silicon particles in the coating solution and stir for 12 h. Wait for the toluene to evaporate and allow the asphalt to coat the surface of the nano-silicon particles.
[0091] (3) The asphalt-coated nano-silicon particles are carbonized in an argon atmosphere at 800°C for 1 h to obtain silicon-carbon composite particles Si / C1.
[0092] (4) Polyvinyl pyrrolidone (PVP), urea, NaCl and Si / C1 were added to deionized water in a mass ratio of 1:1:1:2, stirred for 2 h, and then frozen at -65 °C for 12 h using a freeze dryer. After it became completely solid, it was vacuum dried at -65 °C for 24 h to prepare a Si / C1 / C2 precursor.
[0093] (5) Argon was introduced into the tubular furnace as a protective gas, and the obtained Si / C1 / C2 precursor was calcined at 600°C for 6 h.
[0094] (6) The calcined product was repeatedly washed with deionized water for three times, and then placed in a drying oven and dried at 45° C. for 12 h to obtain a silicon-carbon composite material Si / C1 / C2.
[0095] In the final product, the silicon-carbon composite material Si / C1 / C2, the thickness of the first coating layer is 30 nm, and the thickness of the second coating layer is 150 nm.
[0096] The elastic modulus of the first coating layer and the elastic modulus of the second coating layer are characterized by measuring the elastic modulus of a single particle in the silicon-carbon composite particles Si / C1 and the silicon-carbon composite material Si / C1 / C2. Specifically, a nanoindenter (Hysitron TI 950) is used for testing in accordance with JB / T 12721-2016. Before the test, the particle powder is dispersed in the epoxy resin for curing, and the cured resin is cut by ion polishing. The nanoprobe of the nanoindenter is used to press the single particle, monitor the indentation depth on the particle surface, convert the strength of the single particle, and measure the degree of deformation recovery after removing the load (nanoprobe). The elastic modulus of five particles of the same sample are tested in parallel and the average value is taken.
[0097] The deformation recovery of the silicon-carbon composite particles Si / C1 of this embodiment after the load is removed is 89.4%, the elastic modulus T1 of the first coating layer is 60 GPa, and the elastic modulus T2 of the second coating layer is 10 GPa.
[0098] Embodiment 2, 3, 6, 7
[0099] Examples 2, 3, 6, and 7 provide a silicon-carbon composite material, which is obtained by adjusting the amounts of different raw materials with reference to Example 1. Some parameters of the product are shown in Table 1.
[0100] Embodiment 4, 5, 8, 9
[0101] Examples 4, 5, 8 and 9 provide a silicon-carbon composite material. Referring to Example 1, Examples 4 and 5 respectively use reduced pressure and increased pressure treatment during step (3) carbonization, and Examples 8 and 9 respectively use reduced pressure and increased pressure treatment during step (5) calcination.
[0102] Comparative Example 1
[0103] This comparative example provides a silicon-carbon composite material, which differs from Example 1 in that there is no first coating layer. The preparation process is the same as Example 1, except that steps (1) to (3) are omitted to finally obtain a silicon-carbon composite material Si / C2.
[0104] Comparative Example 2
[0105] This comparative example provides a silicon-carbon composite material, which differs from Example 1 in that there is no second coating layer. The preparation process is the same as Example 1, except that step (4) is omitted, and finally the silicon-carbon composite material Si / C1 is obtained.
[0106] Comparative Examples 3 to 6
[0107] Comparative Examples 3 to 6 respectively provide a silicon-carbon composite material, which is different from Example 1 in that it is obtained by adjusting the amount of different raw materials and the preparation process, and some parameters of the product are shown in Table 1.
[0108] Table 1. Some parameters of examples and comparative examples
[0109]
[0110] Performance Testing
[0111] The batteries prepared in the examples and comparative examples were subjected to relevant performance tests, as follows:
[0112] LiNiCoMnO2, Super P and PVDF are added into N-methylpyrrolidone (NMP) in a mass ratio of 97:1.7:1.3, mixed evenly, coated on the current collector copper foil, dried, cold pressed, trimmed, cut into pieces, divided into strips, and dried again to obtain the positive electrode sheet.
[0113] The silicon-carbon composite material, CNT, sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber of the embodiment or comparative example are added into NMP in a mass ratio of 96:1.3:1.2:1.5 and mixed evenly, coated on the current collector aluminum foil, dried, trimmed, cut into pieces, slit, and dried again for 12 hours to obtain a negative electrode sheet.
[0114] The prepared positive electrode sheet, PE separator and negative electrode sheet are stacked in order so that the separator is between the positive and negative electrode sheets, and then wound to obtain a bare battery cell; the bare battery cell is placed in an aluminum-plastic film outer package, and the electrolyte (1M lithium hexafluorophosphate, ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1) is injected into the dried battery, and then packaged, allowed to stand, formed, shaped and capacity divided to prepare a soft-pack battery.
[0115] In a 25℃ environment, the divided battery is first discharged at 0.2C constant current to 3.0V; then charged at 3C constant current and constant voltage to 4.25V, with a cut-off current of 1.8C; charged at 3C constant current and constant voltage to 4.4V, with a cut-off current of 1.5C; charged at 1.5C constant current and constant voltage to 4.5V, with a cut-off current of 0.05C; then discharged at 0.7C constant current to 3.0V; each charge and discharge should be separated by 5 minutes, and the cycle is repeated. After 300 cycles of charge and discharge, the 300-cycle capacity retention rate is calculated according to the following calculation formula:
[0116] 300-cycle capacity retention rate = (300-cycle discharge specific capacity / first cycle discharge specific capacity) × 100%.
[0117] Test of the expansion rate of the negative electrode sheet at full charge: After the battery has been divided into one circle, discharge it again according to the above process to 5mV, so that the negative electrode sheet is in a fully charged state. Disassemble it in an inert atmosphere and measure the thickness of the negative electrode sheet with a micrometer. The expansion rate of the negative electrode sheet at full charge = the thickness of the negative electrode sheet at full charge / the initial thickness of the negative electrode sheet after pressing.
[0118] The test results are shown in Table 2.
[0119] Table 2. Performance test results
[0120]
[0121] As can be seen from the table, Comparative Example 1 omits the first coating layer, and Comparative Example 2 omits the second coating layer. The deformation recovery rate of both after removing the load has decreased to a certain extent compared with Example 1, while the cycle performance has decreased significantly and the expansion rate is also higher. Example 2 and Example 3 adjusted the ratio of the first carbon source and the solvent. Although the cycle performance has decreased to a certain extent compared with Example 1, the amplitude is relatively low, and the full-charge expansion rate fluctuates to a certain extent. In Example 4, the second coating layer is prepared by evaporation and drying. It can be seen that the effect on the deformation recovery rate after removing the load is not significant, and the cycle performance is slightly reduced compared with Example 1. The elastic modulus of the first coating layer of Example 5 is higher. Examples 6 and 7 adjust the amount of PVP to make the thickness of the second coating layer change to a certain extent, and the cycle performance and full-charge expansion rate also change accordingly. The elastic modulus of the second coating layer of Example 8 and Example 9 is lower or higher than that of Example 1, and the cycle performance and full-charge expansion rate also change accordingly.
[0122] The embodiment adjusts the thickness of the first coating layer by adjusting the mass ratio of asphalt to silicon particles, and adjusts the thickness of the second coating layer by adjusting the mass proportion of polyvinyl pyrrolidone, and finally adjusts the first coating layer thickness H1, the first coating layer elastic modulus T1, the first coating layer thickness H2, and the first coating layer elastic modulus T2 to satisfy 5Z≤(H1×T1+H2×T2) / (H1+H2)≤8Z, that is, the formula value is between 15 and 24. The meaning of this formula is that the sum of the elastic buffering capacity contributed by the first elastic carbon coating layer and the elastic buffering capacity contributed by the second porous carbon coating layer synergistically balances the self-expansion of the silicon particles.
[0123] In addition, comparing Example 1 with Examples 5 to 8, if the first carbon coating layer is too thick, it will be transformed into a hard frame, lose its elastic characteristics, and also restrict the transmission of lithium ions; if it is too thin, it will affect the conductivity, and the buffering capacity will be reduced, and the protection of the silicon core will be weakened; if the second carbon coating layer is too thick, it will cause the carbon framework to polymerize, affecting the generation of a porous structure, thereby reducing the specific surface area of the material and affecting the cycle life retention rate; if it is too thin, the carbon framework will be easily broken, and the reduction in the carbon material content will also reduce the conductivity. Comparing Example 1 with Comparative Example 3, the relative proportion of asphalt in Comparative Example 3 is lower, resulting in the first coating layer being too thin, its elastic buffering capacity is insufficient, the protection of the silicon core is weakened, the cycle capacity retention rate is greatly reduced, and the expansion rate is significantly increased. Comparing Example 1 with Comparative Example 4, the relative proportion of asphalt in Comparative Example 4 is too high, and the first coating layer formed is too thick and will be transformed into a hard frame, losing its elastic characteristics, and will also restrict the transmission of lithium ions. The deterioration of the cycle capacity retention rate and the expansion rate is even worse than that of Comparative Example 3. Comparing Example 1 and Comparative Example 5, the amount of PVP used in Comparative Example 5 is too high, which greatly increases the thickness of the second carbon coating layer, and the carbon framework polymerization affects the formation of the porous structure. The specific surface area of the material is reduced, which has a greater impact on the cycle performance; Comparing Example 1 and Comparative Example 6, the amount of PVP used in Comparative Example 6 is too low, which makes the second carbon coating layer too thin, the carbon framework structure is easily broken, and the reduction in carbon material content will also reduce conductivity, so the cycle capacity retention rate and expansion rate performance are far inferior to Example 1.
[0124] The present application is described in detail above in conjunction with the embodiments, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
Claims
1. A silicon-carbon composite material, characterized in that: include: Carbon-silicon composite particles, the carbon-silicon composite particles comprising silicon particles and a first coating layer coating the silicon particles, the first coating layer comprising elastic carbon, and the carbon-silicon composite particles recovering a deformation S of ≥80% after the load is removed; A second coating layer, wherein the second coating layer coats the carbon-silicon composite particles, and the second coating layer comprises a porous carbon framework.
2. The silicon-carbon composite material according to claim 1, characterized in that: The silicon particles are at least one of nano silicon particles and micro silicon particles. The thickness H1 of the first coating layer is 20-40 nm, and the thickness H2 of the second coating layer is 100-200 nm.
3. The silicon-carbon composite material according to claim 2, wherein the elastic modulus of the first coating layer is T1, the elastic modulus of the second coating layer is T2, the self-expansion rate Z of the silicon particles is ≥ 300%, and the silicon-carbon composite material satisfies the following relationship: In the above relationship, H1 and H2 are values in nm without measuring weights, T1 and T2 are values in GPa without measuring weights, and Z is the actual value of the percentage. 4 . The silicon-carbon composite material according to claim 3 , wherein the elastic modulus T1 of the first coating layer is 40 to 80 GPa, and the elastic modulus T2 of the second coating layer is 8 to 15 GPa.
5. The method for preparing the silicon-carbon composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: coating the surface of silicon particles with a first carbon source and carbonizing the particles to obtain carbon-silicon composite particles; The carbon-silicon composite particles are mixed with a second carbon source and a pore-forming agent, freeze-dried, and calcined to form a second coating layer to obtain the silicon-carbon composite material; Preferably, coating the first carbon source on the surface of the silicon particles comprises: mixing the first carbon source with a first solvent to obtain a coating solution; Mixing and stirring the silicon particles and the coating solution, and allowing the first solvent to volatilize so that the first carbon source is coated on the surface of the silicon particles; Preferably, the mass volume ratio of the first carbon source to the first solvent is (0.1-0.5) g:15 mL; Preferably, the first solvent comprises toluene.
6. The preparation method according to claim 5, characterized in that: The first carbon source is asphalt; Preferably, the asphalt is selected from at least one of petroleum asphalt, coal asphalt and natural asphalt; Preferably, the mass ratio of the first carbon source to the silicon particles is (1-9):3; Preferably, the carbonization temperature is 500-1000°C; Preferably, the carbonization time is 15 min to 4 h.
7. The preparation method according to claim 5, characterized in that: The mass ratio of the second carbon source to the pore-forming agent is 1:(0.1-0.5); Preferably, the second carbon source comprises at least one of polyvinyl pyrrolidone, polyvinyl alcohol, sucrose, glucose, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyethylene glycol; Preferably, the pore-forming agent includes at least one of NaCl, KCl, urea and ammonium bicarbonate.
8. The preparation method according to claim 5, characterized in that: The freeze drying temperature is -90 to -20°C, and / or the calcination temperature is 500 to 800°C; Preferably, the freeze drying comprises freezing at the temperature for 8 to 24 hours and then vacuum drying; Preferably, the vacuum drying time is 24 to 72 hours; preferably, the calcination time is 3 to 12 hours.
9. A secondary battery, characterized in that: The silicon-carbon composite material comprises the silicon-carbon composite material according to any one of claims 1 to 4, or the silicon-carbon composite material obtained by the preparation method according to any one of claims 5 to 8.
10. Electrical equipment, characterized in that: A secondary battery comprising the secondary battery according to claim 9.
Citation Information
Patent Citations
Graphene composite material and preparation method thereof
CN108232139A
Preparation method of silicon-carbon composite material coated by multiple layers of carbon
CN110085850A
High-performance silicon-carbon composite negative electrode material with adjustable and controllable particle size and preparation method thereof
CN110931756A
Secondary coated silicon-carbon composite material, preparation method thereof, and electrode and electrochemical device using secondary coated silicon-carbon composite material
CN112242503A
Silicon-carbon composite material, preparation method thereof, negative plate and lithium secondary battery
CN115513432A